STUDI LITERATUR TENTANG HUBUNGAN ANTARA MOTIVASI EKSTRINSIK DAN INTRINSIK DENGAN KINERJA DAN KESEJAHTERAAN KARYAWAN - Liena Prajogi; Dewi Melati; Taufik Hidayat; Tri Yuni Susilowati (MANAJEMEN DEWANTARA, 2025)
This study aims to explore the relationship between extrinsic and intrinsic motivation and their impact on employee performance and well-being. Drawing on Self-Determination Theory (SDT), this research emphasizes that both types of motivation are essential drivers influencing employees’ engagement, creativity, and intention to stay within an organization. While extrinsic motivation is often linked to compensation, performance-based incentives, workload, and communication effectiveness, intrinsic motivation is shaped by empowerment, recognition, and competence development. Understanding these factors provides a more holistic perspective on managing human resources in a dynamic work environment. This research employs a qualitative literature review method, analyzing 40 selected scientific publications from 2020–2025 obtained through databases such as Google Scholar, Scopus, and ScienceDirect. The articles were reviewed and thematically analyzed to identify patterns, similarities, and differences in the findings regarding how extrinsic and intrinsic motivations interact in the workplace context. The findings indicate that extrinsic motivation ensures employees’ sense of security, fairness, and recognition, while intrinsic motivation fosters creativity, commitment, and sustainable engagement. When applied together, both types of motivation complement each other in enhancing performance and well-being. Organizations are therefore encouraged to balance extrinsic and intrinsic motivators to create sustainable productivity and long-term employee satisfaction